Evaluation of a protein deficient diet in rats through blood oxidative stress biomarkers - Prada, F. J A; Macedo, D. V.; De Mello, Maria Alice Rostom [UNESP] (My University, 2003)
Protein malnutrition leads to functional impairment in several organs, which is not fully restored with nutritional recovery. Little is known about the role of oxidative stress in the genesis of these alterations. This study was designed to assess the sensitivity of blood oxidative stress biomarkers to a dietary protein restriction. Male Wistar rats were divided into two groups, according to the diet fed from weaning (21 days) to 60 day old: normal protein (17% protein) and low protein (6% protein). Serum protein, albumin, free fatty acid and liver glycogen and lipids were evaluated to assess the nutritional status. Blood glutathione reductase (GR) and catalase (CAT) activities, plasma total sulfhydryl groups concentration (TSG) as well as plasma thiobarbituric acid reactive substances (TBARs) and reactive carbonyl derivatives (RCD) were measured as biomarkers of the antioxidant system and oxidative damage, respectively. The glucose metabolism in soleus muscle was also evaluated as an index of stress severity imposed to muscular mass by protein malnutrition. No difference was observed in muscle glucose metabolism or plasma RCD concentration between both groups. However, our results showed that the low protein group had higher plasma TBARs (62%) concentration and lower TSG (44%) concentration than control group, indicating increased reactive oxygen species production in low protein group. The enhancement of erythrocyte GR (29%) and CAT (28%) activities in this group also suggest an adaptation to the stress generated by the protein deficiency. Taken together, the results presented here show that the biomarkers used were able to reflect the oxidative stress level induced by this specific protein deficient diet.
Keywords: Adaptation to stress; Blood catalase; Blood glutathione reductase; Nutritional recovery; Oxidative stress; Protein malnutrition; Stress generated by protein deficiency; Sulfhydryl groups; TBARs; Wistar rats; antioxidant; biological marker; carbonyl derivative; catalase; fatty acid; glutathione reductase; reactive oxygen metabolite; thiobarbituric acid; thiobarbituric acid derivative; thiol derivative; adaptation; albumin blood level; animal experiment; controlled study; glucose metabolism; male; muscle mass; nonhuman; nutritional status; oxidative stress; priority journal; protein blood level; protein deficiency; protein malnutrition; protein restriction; rat; rat strain; soleus muscle; weaning; Adaptation, Physiological; Animals; Biological Markers; Catalase; Glucose; Glutathione Reductase; Male; Nutritional Status; Oxidative Stress; Protein Deficiency; Rats; Rats, Wistar; Sulfhydryl Compounds; Thiobarbituric Acid Reactive Substances